Strength of Binary and Ternary Blended Cement Pastes Containing Palm Oil Fuel Ash and Metakaolin Exposed To Sodium Sulphate - Ismail, Mohd Hanif; Othman, Nor Hazurina; Mohd Ali, Ahmad Zurisman; Megat Johari, Megat Azmi; Ariffin, Kamar Shah (EDP Sciences, 2017)
The compressive strength of binary (BBCP) and ternary blended cement pastes (TBCP) containing Palm Oil Fuel Ash (POFA) and Metakaolin (MK) exposed to 3 % sodium sulphate solution has been studied. The ordinary Portland cement (OPC) was partially replaced with POFA and MK on mass-for-mass basis. All specimens were first cured for 28 days in normal water and subsequently subjected to full immersion in sodium sulphate solution for 150 days for the compressive strength evaluation. The results show that partial replacement of cement with POFA and MK improved the durability of the cement pastes by reducing the damage caused by sulphate attack.